EC-VAD: Combined Use of Extracorporeal Membrane Oxygenation and Percutaneous Microaxial Pump Left Ventricular Assist Device. Issue 3 (March 2019) - Akanni, Olutosin J.; Takeda, Koji; Truby, Lauren K.; Kurlansky, Paul A.; Chiuzan, Codruta; Han, Jiho; Topkara, Veli K.; Yuzefpolskaya, Melana; Colombo, Paolo C.; Karmpaliotis, Dimitrios; Moses, Jeffery W.; Naka, Yoshifumi; et al.
Abstract : Combination of venoarterial extracorporeal membrane oxygenation (VA-ECMO) and a percutaneous microaxial left ventricular assist device (pLVAD), or "EC-VAD, " has been reported in cases of left ventricular decompression with mixed results. We conducted a retrospective review of patients who received EC-VAD (n = 29) or isolated VA-ECMO therapy (ECMO-only; n = 196) for refractory cardiogenic shock between February 2011 and October 2014. Fourteen patients received VA-ECMO and then Impella pLVAD (E→EC-VAD), and 15 received the Impella pump then VA-ECMO (I→EC-VAD). E→EC-VAD patients demonstrated decreased pulmonary artery systolic (36.00 ± 16.84 mm Hg versus 30.63 ± 12.13 mm Hg; p = 0.049) and diastolic (24.25 ± 13.45 mm Hg versus 17.25 ± 7.96 mm Hg, p = 0.049) pressures by 24 hours post-EC-VAD implant. In the same period, I→EC-VAD patients demonstrated improved SvO2 (43.14 ± 16.75% versus 75.18 ± 13.88%, p = 0.043) and PaO2/FiO2 ratio (148.55 ± 67.69 mm Hg versus 374.51 ± 170.97 mm Hg, p = 0.043). Thirty-day survival rates were 42.9% in E→EC-VAD, 46.7% in I→EC-VAD, and 49.0% in ECMO-only ( p = 0.913). Hemolysis occurred more in EC-VAD patients (44.83% versus 17.35% in ECMO-only, p = 0.002); however, there was no increased frequency of other adverse events including bleeding and lower limb ischemia. Despite increased hemolysis, combined use of VA-ECMO and pLVAD may improve or circumvent left ventricular distension in refractory cardiogenic shock while promoting adequate blood flow.